2021
DOI: 10.3390/jcm10153305
|View full text |Cite
|
Sign up to set email alerts
|

One Year after Mild COVID-19: The Majority of Patients Maintain Specific Immunity, But One in Four Still Suffer from Long-Term Symptoms

Abstract: After COVID-19, some patients develop long-term symptoms. Whether such symptoms correlate with immune responses, and how long immunity persists, is not yet clear. This study focused on mild COVID-19 and investigated correlations of immunity with persistent symptoms and immune longevity. Persistent complications, including headache, concentration difficulties and loss of smell/taste, were reported by 51 of 83 (61%) participants and decreased over time to 28% one year after COVID-19. Specific IgA and IgG antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 33 publications
4
48
0
1
Order By: Relevance
“…Our data illustrate that SARS-CoV-2-specific T cells against SARS-CoV-2 epitopes were detectable over the entire course of the study, and showed most stable frequencies for SARS-CoV-2 S1 while values for SARS-CoV-2 S2 initially decreased and then remained stable. As already stated in previous research, SARS-CoV-2-specific T cells have been successfully detected for a period of up to 12 months post symptom onset ( 8 10 , 12 , 26 ). However, few studies have assessed T cell frequencies against SARS-CoV-2 M, N, and S separately over a period as long as 1 year.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our data illustrate that SARS-CoV-2-specific T cells against SARS-CoV-2 epitopes were detectable over the entire course of the study, and showed most stable frequencies for SARS-CoV-2 S1 while values for SARS-CoV-2 S2 initially decreased and then remained stable. As already stated in previous research, SARS-CoV-2-specific T cells have been successfully detected for a period of up to 12 months post symptom onset ( 8 10 , 12 , 26 ). However, few studies have assessed T cell frequencies against SARS-CoV-2 M, N, and S separately over a period as long as 1 year.…”
Section: Discussionsupporting
confidence: 66%
“…Data from SARS and Middle East Respiratory Syndrome (MERS) epidemics suggest that cellular immunity to these viruses can last for many years ( 6 , 7 ), but for SARS-CoV-2, this has yet to be investigated. Recent studies detected the presence of cellular immunity as well as humoral immunity for up to twelve months post infection ( 8 12 ). Nevertheless, it is highly challenging to determine reliable correlates of sufficient immunological protection against reinfection, severe disease, or other outcomes ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…We show that IFNγ+ T-cell responses after infection are remarkably stable between three and twelve months post-infection (Figure 1A). In longitudinal studies, we and others have previously shown significant decreases in the IFNγ response up to twelve months after infection [8,9,18]. The results shown here nevertheless underline the marginal decline of such responses, particularly a biphasic decline with a strong decrease in the first three months, followed by a comparably stable second phase indicative of durable cellular immunity.…”
Section: Discussionsupporting
confidence: 66%
“…Rather, the levels of IFNγ+ T-cells, which are reportedly lower in patients with severe than mild infection [15], are presented to put the surprisingly low IFNγ+ T-cell responses from three months into context. We previously demonstrated that the duration of acute phase symptoms correlates with levels of cellular immunity [18]. Given that most of the patients in cohort 3 described here had mild COVID-19, our comparison is limited to patients with mild COVID-19 compared with persons vaccinated with BioNTech/Pfizer BNT162b2.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review reported that symptoms of mild COVID-19 may persist after 3 weeks in a third of patients (van Kessel et al, 2021). Another study reported that up to one in four patients with mild COVID-19 were still experiencing symptoms after 1 year (Rank et al, 2021); however, data on the exact prevalence and long-term effects of long COVID are still lacking (Zarei et al, 2021), with an urgent need for research in different populations and settings (Michelen et al, 2021). To aid clinicians and researchers, on October 6, 2021, the World Health Organization (WHO) issued a clinical case definition of post-COVID-19 condition, obtained by a Delphi consensus (WHO, 2021), as follows: "Post-COVID-19 condition occurs in individuals with a history of probable or confirmed SARS-CoV-2 infection, usually 3 months from the onset of COVID-19 with symptoms that last for at least 2 months and cannot be explained by an alternative diagnosis.…”
Section: Introductionmentioning
confidence: 99%